FORMULATION AND EVALUATION OF ATORVASTATINCALCIUM LOADED CHITOSAN NANOPARTICLES - J. B. VARUNA KUMARA,; BASAVARAJ MADHUSUDHAN, (International Journal of Pharma and Bio Sciences, 2015)
Atorvastatin happens to be a potential inhibitor of HMG-CoA reductase involved in the synthesis of cholesterol and is being used to decrease the low-density lipoproteins in blood. The drug has profound effect, but the dosage is high compared to other statins. Therefore, it was thought to minimize the frequency of doses to avoid the possibility of drug resistance by atorvastatin and deliver using nanocarriers. The aim of this research was to characterize and evaluate the atorvastatin-loaded chitosan nanoparticles before delivery. The nanoparticles were prepared by ionic gelation. The sizes were visualized by dynamic laser light scattering method. The size of the nanoparticles ranged between 220 and 314 nm. Upon considering the encapsulation efficiency, 50% were found to be the least and 75% the most. The formulation exhibited a slow and sustained release (~76%) of atorvastatin from the nanoparticles in <12 hours. The atorvastatin-loaded chitosan nanoparticles were stable, hemocompatible and found to be fit for drug delivery.